Two new phthalide derivatives from the endophytic fungus Penicillium vulpinum isolated from Sophora tonkinensis. Issue 3 (1st February 2021) - Qin, Yuyue; Liu, Xiaobo; Lin, Jing; Huang, Jingying; Jiang, Xiaofei; Mo, Tuxiang; Xu, Zhaolong; Li, Jun; Yang, Ruiyun
Abstract: Two new phthalide derivatives, (-)-3-carboxypropyl-7-hydroxyphthalide (1 ) and (-)-3-carboxypropyl-7-hydroxyphthalide methyl ester (2 ), were isolated from the endophytic fungus Penicillium vulpinum isolated from the Chinese medicinal plant Sophora tonkinensis . Their structures were elucidated using spectroscopic methods, mainly on 1D and 2D NMR. Compound 1 exhibited medium antibacterial activities against Bacillus subtilis, Shigella dysenteriae and Enterobacter areogenes with MIC values of 12.5-25 μg/mL, and 2 showed a medium inhibition to E. areogenes with MIC value of 12.5 μg/mL. Graphical Abstract: